Determinants of Tax Evasion in Micro Small Medium Enterprises: An Explanation of Ethics Theory - Selfira Salsabilla (Jurnal Proaksi, 2025)
Main Purpose - The purpose of this study was to examine the effect of perceived benefits and moral obligations on tax evasion by Micro, Small, and Medium Enterprises.Method - This research is a quantitative study with a survey method. The population of this research consists of MSMEs in the Special Region of Yogyakarta (DIY), with the sample selected using a convenience sampling technique. The study involved 144 MSMEs. The data was analysed using the Structural Equation Model with the help of SmartPLS software. Main Findings - The results of data analysis show that perceived benefits have a significant positive effect on tax evasion. Meanwhile, moral obligation has a negative effect on tax evasion. This means that it is necessary to reduce the perception of benefits and increase moral obligation to reduce tax evasion.Theory and Practical Implications - The government needs to strive to increase moral obligations and reduce the perception of benefits so that MSMEs do not engage in tax evasion. Socialization programs need to be designed not only to provide technical information on tax calculation and reporting, but also to include knowledge that addresses the ethics of MSME owners and managers. Novelty - This article offers an examination of the factors that influence tax evasion on MSMEs in Indonesia as a developing country, with the framework of Ethical Theory.